أهمية التعليم الإسلامي المعتدل في التغلب على أعمال القرن الحادي والعشرين الألفي التحرري على تأثير الثقافة الأجنبية - Ahmad Taufiq; Arrum Wijaya (Vol. 1 No. 1 (2022): Proceeding of International Conference Cultures & Languages 2022, 2022)
This study aims to: (1) Identify the liberal actions of the 21st century millennial generation due to the influence of foreign cultures. (2) Describe the urgency of religious moderation education in overcoming the liberal actions of the millennial generation of the 21st century. This study uses a qualitative research type with a literature study method with a phenomenological approach. The results of this study indicate that (1) the millennial generation does not have strong self-control in responding to foreign cultural developments, causing low religious moderation for the 21st century millennial generation in terms of faith and morals due to their lack of control in responding to foreign cultures. (2) Low moderation millennial generation can be overcome by providing education to them. Education in Islamic moderation can be carried out by community leaders such as the government, religious and cultural leaders, parents and families. The results of this study indicate that Islamic moderation education is very important given to the millennial generation of the 21st century as an effort to overcome the low level of Islamic moderation and as a form of effort to control the liberal attitude of teenagers towards the development of foreign cultures in Indonesia.